APLIKASI ASESMEN LEMBAGA SERTIFIKASI PROFESI POLIBATAM BERBASIS WEBSITE - Agus Fatulloh; Hendro Hendro (G-Tech: Jurnal Teknologi Terapan, 2021)
The Professional Certification Institute Polibatam is an institution implementing professional certification activities for Polibatam students. The current certification assessment process is still carried out conventionally, namely by way of the assessment coming to the LSP location, submitting documents, and filling out data on the forms provided, the assessor will determine the assessment schedule, make questions and recap the assessment results so that all of this series of activities will take time plus have to save documents in physical form which later can cause new problems such as lost, scattered, damaged, and difficulty if you want to find the document. The assessment application of the Polibatam Professional Certification Institute was built with the aim of helping and facilitating the entire series in the implementation of the assessment, both from the assessor's side and from the assessor's side. The application was developed using the waterfall method, measurement of application testing on user acceptance using the user acceptance testing (UAT) method by distributing questionnaires which was then calculated using a Likert scale. From the results of the development and measurements carried out on the application, it was found that the assessment application of the Polibatam Professional Certification Institute was able to facilitate the implementation of the assessment properly and could assist in managing data on assessment questions, scheduling, checking the results of the assessment easily, and based on the calculation of the results by the questionnaire it also showed an average value acceptance index is above 90%.